2015
DOI: 10.1016/j.neurobiolaging.2014.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease associates with higher brain amyloid load in normal elderly

Abstract: Background The accumulation of amyloid β plaques (Aβ) is a central feature of Alzheimer’s disease (AD). First reported in animal models, it remains uncertain if peripheral inflammatory/infectious conditions in humans can promote Aβ brain accumulation. Periodontal disease, a common chronic infection, has been previously reported to be associated with AD. Methods Thirty-eight cognitively normal, healthy, community residing elderly (mean age 61; 68% female) were examined in an Alzheimer’s Disease research cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(171 citation statements)
references
References 87 publications
3
163
0
5
Order By: Relevance
“…In addition, antibody levels to Fusobacterium nucleatum and Prevotella intermedia , which are oral flora organisms, are significantly increased in serum collected at baseline before AD onset in AD patients compared to controls [14]. Periodontal disease, which is defined by clinical attachment loss, is associated with brain Aβ load [34]. Leptomeningeal cells transfer peripheral inflammatory signals from macrophages activated by lipopolysaccharides from Porphyromonas gingivalis , which is a major etiological agent of periodontal disease, to microglial cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antibody levels to Fusobacterium nucleatum and Prevotella intermedia , which are oral flora organisms, are significantly increased in serum collected at baseline before AD onset in AD patients compared to controls [14]. Periodontal disease, which is defined by clinical attachment loss, is associated with brain Aβ load [34]. Leptomeningeal cells transfer peripheral inflammatory signals from macrophages activated by lipopolysaccharides from Porphyromonas gingivalis , which is a major etiological agent of periodontal disease, to microglial cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…First, there are significant correlations between the rate of cognitive decline and measures of periodontal disease progression, such as pocket depth, alveolar bone loss and tooth loss [37]. Currently, the relevance of newly identified risk factor, cognitive deficit for periodontitis [8], is more difficult to measure and pinpoint.…”
Section: Periodontal Diseasementioning
confidence: 99%
“…With regard specifically to periodontal disease, one longitudinal study has suggested a link between higher Aβ load in the hippocampus of elderly humans with mild forms of periodontitis [37]. Singhrao et al [58] are suggesting the role of P. gingivalis in inflammation mediated injury with progressive deterioration of the hippocampal microvascular integrity in the very regions of the brain that demonstrate a high burden of neuropathological hallmarks of AD.…”
Section: The Blood-brain Barriermentioning
confidence: 99%
“…More recent reports relating infections to a causative role in the onset of dementia are supported by Kamer et al [129] suggesting that mild periodontitis is associated with higher brain amyloid load in normal elderly subjects in the hippocampus.…”
Section: Alzheimer's Diseasementioning
confidence: 84%